2014
DOI: 10.1364/ol.39.005435
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical tuning of modified-geometry resonators clad in blue phase liquid crystals

Abstract: Active optical tuning of silicon racetrack resonators clad in dye-doped blue phase liquid crystals (BPLCs) is experimentally demonstrated. An adiabatic racetrack resonator geometry that allows for enhanced tuning is presented and analyzed. The resonance shift of an unmodified geometry racetrack is Δλ=0.7 nm, while an adiabatic racetrack achieves a Δλ=1.23 nm resonance shift because of a greater mode overlap with the cladding. The calculated refractive index change of the BPLC is Δn=0.0041 for both geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, the structure may be optimized to operate over a wider bandgap. Tunability with the incorporation of for example, liquid crystals [86][87][88][89][90], can also be utilized to mitigate the bandwidth issue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the structure may be optimized to operate over a wider bandgap. Tunability with the incorporation of for example, liquid crystals [86][87][88][89][90], can also be utilized to mitigate the bandwidth issue.…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of resonant interactions occur between an optical field and the electrons of a plasmonic (metal) material [61][62][63][64][65][66][67][68][69][70][71][72]: (a) Surface Plasmon Resonance (SPR) -associated with collective oscillations of the electrons near the surface; (b) Localized Surface Plasmon Resonances [LSPR) -associated with light interaction with isolated metal nanoparticles. Tunability of the optical properties of plasmonic nanostructures with liquid crystals can be accomplished by either (a) dissolving or suspending nano-size plasmonic particles in bulk NLC cell, or (b) incorporating LC in plasmonic nanostructures.…”
Section: Tunable Plasmonic Nanostructures Micro-ring Resonators and E...mentioning
confidence: 99%
“…It has been suggested that the diffraction power could be improved by eight times larger, yielding a n 2 of *0.5 cm 2 /W [146]. Ptasinski et al recently designed an adiabatic racetrack resonator clad in the dye doped BP to achieve all-optical modulation [147]. Under the illumination of a broadband blue LED (λ * 470 nm), the resonant wavelengths shifted 1.23 nm at maximum.…”
Section: Nonlinear Optical Response Of Bpsmentioning
confidence: 99%